The locker ate Lucy! - Chabert, Jack (Chabert, Jack. Eerie Elementary., 2014)
Only a week into his job as hall monitor and class protector, Sam Graves and his friends Lucy and Antonio are trying to uncover the secrets of Eerie Elementary, their living and malevolent school--and then Lucy gets eaten by her locker.